Integrated Management of Systems, Services, Processes and People in IT 20th IFIP/IEEE International Workshop on Distributed Systems: Operations and Management, DSOM 2009, Venice, Italy, October 27-28, 2009. Proceedings - Bartolini, Claudio.; Gaspary, Luciano Paschoal. (Lecture Notes in Computer Science, 2009)
This book constitutes the refereed proceedings of the 20th IFIP/IEEE International Workshop on Distributed Systems: Operations and Management, DSOM 2009, held in Venice, Italy, on October 27-28, 2009, as part of the 5th International Week on Management of Networks and Services, Manweek 2009. The 14 revised full papers presented were carefully reviewed and selected from 50 submissions. The papers are organized in topical sections on monitoring and analysis tools, service management, autonomic and self-management, and security and virtualization.